2019
DOI: 10.3390/molecules24193588
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Porous Activated Carbons for High Performance Supercapacitors from Taixi Anthracite by Multi-Stage Activation

Abstract: Coal-based porous materials for supercapacitors were successfully prepared using Taixi anthracite (TXA) by multi-stage activation. The characterization and electrochemical tests of activated carbons (ACs) prepared in different stages demonstrated that the AC from the third-stage activation (ACIII) shows good porous structures and excellent electrochemical performances. ACIII exhibited a fine specific capacitance of 199 F g−1 at a current density of 1 A g−1 in the three-electrode system, with 6 mol L−1 KOH as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 53 publications
(62 reference statements)
0
11
1
Order By: Relevance
“…It was confirmed that the largest contribution to SSA is from the micropores. As the number of micropores in the sample is increased, the larger the SSA becomes, and the more mesopores of the samples are included, the larger the D ave , at the expense of a smaller SSA …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was confirmed that the largest contribution to SSA is from the micropores. As the number of micropores in the sample is increased, the larger the SSA becomes, and the more mesopores of the samples are included, the larger the D ave , at the expense of a smaller SSA …”
Section: Resultsmentioning
confidence: 99%
“…According to the results of pore structure analysis, it can be concluded that both impregnation ratio and multistage activation temperatures are significant for the SSA and V total development of the ABACs. Therefore, the combination of multistage activation temperature and a suitable impregnation ratio is important in the optimization of pore textural properties of the ABACs …”
Section: Resultsmentioning
confidence: 99%
“…Among the simplest and most efficient methods of human body detoxification is enterosorption [ 4 , 5 ], a procedure for the immobilization and elimination of endogenous and exogenous metabolites from the human body [ 6 , 7 , 8 ]. Today, this method is largely employed by the majority of health clinics, the removal of poisonous species relying usually on activated carbons, lignocellulosic charcoals, animal bone charcoals, inorganic porous minerals, bone polymeric and silicon-based resins [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, previous studies have shown that multi-stage activation during production improved the property of ACs and their performance. The enhanced specific surface area and pore volume, compared to single-stage activation, was reported for the two-stage activation of anthracite by heat and KOH [ 30 ], of Acer truncatum seed shells by KOH and heat [ 31 ], of brewer’s spent grains by H 3 PO 4 and KOH [ 32 ], of the cotton stalk by KOH and heat [ 33 ], and of soybean stalk by KOH and heat [ 34 ]. These also suggest the potential of the additional thermal treatment of already prepared ACs to improve adsorption.…”
Section: Introductionmentioning
confidence: 99%